Pengaruh Tingkat Kecanduan Media Sosial terhadap Perilaku Mabuk Gawai di Antara Teman Sebaya - Salsa Septi Rahmadhani; Moh. Mudzakkir (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the influence of the level of social media addiction on gadget intoxication behavior among adolescents in the city of Surabaya. The approach used was quantitative with a survey method, involving 286 adolescent respondents aged 17–19 years who actively use social media every day. The research instrument was compiled based on indicators from the theory of behavioral addiction and analyzed using Pearson correlation test and simple linear regression. The results of the study showed that the level of social media addiction was in the high category and had a positive and significant influence on gadget drunk behavior. A correlation coefficient of 0.682 and an influence contribution of 46.5% showed that almost half of the variation in gadget drunk behavior was influenced by social media addiction. In addition, relationships with peers also reinforce these behavioral tendencies through social pressure and digital conformity. This research emphasizes the importance of digital literacy, self-regulation, parental supervision, and the active role of schools and society in preventing adolescents' addictive behavior towards gadgets and excessive use of social media.